Fundamentals of Power Electronics - Erickson, Robert W.; Maksimovic, Dragan (Springer, 2000)
The objective of the First Edition was to serve as a textbook for introductory power electronics courses where the fundamentals of power electronics are defined, rigorously presented, and treated in sufficient depth so that students acquire the knowledge and skills needed to design practical power electronic systems. The First Edition has indeed been adopted for use in power electronics courses at a number of schools. An additional goal was to contribute as a reference book for engineers who practice power electronics design, and for students who want to develop their knowledge of the area beyond the level of introductory courses. In the Second Edition, the basic objectives and philosophy of the First Edition have not been changed. The modifications include addition of a number of new topics aimed at better serving the expanded audience that includes students of introductory and more advanced courses, as well as practicing engineers looking for a reference book and a source for further professional development. Most of the chapters have been significantly revised and updated. Major additions include a new Chapter 10 on input filter design, a new Appendix B covering simulation of converters, and a new Appendix C on Middlebrook's Extra Element Theorem. In addition to the introduction of new topics, we have made major revisions of the material to improve the flow and clarity of explanations and to provide additional specific results, in chapters covering averaged switch modeling, dynamics of converters operating in discontinuous conduction mode, current mode control, magnetics design, pulse-width modulated rectifiers, and resonant and soft-switching converters. A completely new Chapter 10 covering input filter design has been added to the second addition. The problem of how the input filter affects the dynamics of the converter, often in a manner that degrades stability and performance of the converter system, is explained using Middlebrook's Extra Element Theorem. This design-oriented approach is explained in detail in the new Appendix C. Simple conditions are derived to allow filter damping so that converter transfer functions are not changed. Complete results for optimum filter damping are presented. The chapter concludes with a discussion about the design of multiple-section filters, illustrated by a design example.